USING WHATSAPP MESSENGER AS AN INTERPERSONAL COMMUNICATION MEDIA BETWEEN PARENTS AND TEACHERS IN INFORMING CHILDREN'S LEARNING ACTIVITIES AT SCHOOL - Meisyaroh, Siti (Jurnal Komunikasi dan Bisnis, 2022)
This research concerns the use of the "Whatsapp Messenger" application as a communication medium for parents and teachers in an Islamic kindergarten in North Jakarta. The concepts used for this study are Communication Technology, Communication Media, the role of parents in children's learning, and the role of teachers in children's learning. The research method used is a qualitative method. The assessment method used in this research is a case study. In conducting this research, researchers collected various data from various sources using interviews and documentation techniques. The resource persons interviewed by the researchers were teachers and parents of students.